I love you Vaatelainaamo, but some things can be improved: Analysis of motivations, barriers and opportunities in a Finnish service for sharing clothes (ModaPalavra e-periódico, 2017)
This paper presents the results of research conducted with users of a Finnish service for sharing clothes (Vaatelainaamo), which aimed to understand motivations, barriers and opportunities for adoption of consumer practices in the Sharing Economy. The research is based on the interpretive paradigm and phenomenological study, using open questionnaires as data collection method. Among the results, we can point out that the weak sense ofco-ownership, neglect in caring for the clothes and the unavailability of products and even the service are factors that damage the relationship of users with the service. On the other hand, the main motivations for becoming a member of this service are: environmental awareness appreciation of local production and the provision of access to considered expensive items, allowing the possibility of experimentation, associated with pleasure to use different clothes with less environmental impact. Thus, Vaatelainaamo offers an environmentally and economically beneficial solution to the users’ lifestyle, promoting the feeling of belonging, which is the main factor for they love this service, although some aspects can be improved.
Keywords: sharing economy; service design; sustainability